Estudo microestrutural da cerâmica utilitária com a adição de chamote produzida em Icoaraci (Belém-PA) - SOUZA, Misheila dos Santos (2019)
Due to the large amount of ceramic residue that is discarded because of defects in the parts after the firing, the technique of insertion of this crushed ceramic, known as chamote, to the ceramic mass in natura, is used in order to improve the properties of ceramic pieces. It has been observed in previous works that the insertion of chamote in suitable proportions in the mass facilitates the drying providing the reduction of the linear retraction. Icoaraci, District located in the municipality of Belém-PA, is recognized nationally and even outside the country by the production of ceramic handicrafts, its productions range from decorative elements to utilitarian elements. The main utilities are glasses, dishes, pots, bowls, vases, etc. However, it has been observed that in particular the produced pans can not be carried to the fire, because they do not have refractory properties. In order to solve this question, it was observed that in the municipality of Bragança, located in the northeast of the state Pará, refractory pans are produced using chamote in the ceramic mass. Thus, in the present work the chamote mixed in the clay was used in order to observe how the ceramics present themselves with the incorporation of the chamote. The specimens were made with addition of chamotte in percentages of 5%, 10%, 15% and 20% to the ceramic mass in natura. After the firing, the physical properties of the materials were determined by water absorption, apparent porosity, apparent specific mass, and for the study of the microstructure, the tests were performed by Scanning Electron Microscopy (SEM) with the aid of EDS (Energy Dispersive X -ray Detector). From the results of the physical tests, it was verified that the proportion with 10% of chamote, obtained the best results after the firing, which corroborates with the morphology of this proportion.